2019
DOI: 10.1038/s41416-019-0385-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive values of colorectal cancer alarm symptoms in the general population: a nationwide cohort study

Abstract: BACKGROUND: Alarm symptoms are used in many cancer referral guidelines. The objectives were to determine the 1-year predictive values (PVs) of colorectal cancer (CRC) alarm symptoms in the general population and to describe the proportion of alarm symptoms reported prior to diagnosis. METHODS: A nationwide prospective cohort of 69,060 individuals ≥40 years randomly selected from the Danish population was invited to complete a survey regarding symptoms and healthcare-seeking in 2012. Information on CRC diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…Compared with previous studies on symptom prevalence in the general population, we found that the response rate in our study was comparable or even higher 23,24 . Similar to the findings of this study, we found that the PPVs of gastrointestinal alarm symptoms are low in other DaSC studies 14,15 . Compared with a study on respiratory symptoms in a general population in Britain 25 , we found lower rates of cough and dyspnoea.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Compared with previous studies on symptom prevalence in the general population, we found that the response rate in our study was comparable or even higher 23,24 . Similar to the findings of this study, we found that the PPVs of gastrointestinal alarm symptoms are low in other DaSC studies 14,15 . Compared with a study on respiratory symptoms in a general population in Britain 25 , we found lower rates of cough and dyspnoea.…”
Section: Discussionsupporting
confidence: 92%
“…Our analyses of the socioeconomic characteristics of eligible individuals aged ≥40 demonstrate that respondents were younger and with higher rates of cohabitation and labour market affiliation, higher educational and income levels, and were more often of Danish ethnicity when compared with non-respondents. The details of the analyses are reported elsewhere 15 . A total of 20% of the respondents stated that they were daily smokers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations